The sum of cubes is given as:
a³ + b³ = (a + b)(a² - ab + b²)
Example for the sum of cubes:
64x³+y³ ⇒ This is the sum of cubes because each term; 64, x³, and y³ are cube numbers
By writing each term as an expression of cube numbers, we have:
(4x)³ + (y)³ ⇒ 64 is 4³
Use the factorization of the sum of cubes, we have:
(4x + y) ( (4x)²- 4xy + y²)
(4x + y) (16x² - 4xy + y²)
--------------------------------------------------------------------------------------------------------------
The difference of cubes can be factorized as:
(x³ - y³) = (x - y)(x² + xy + y²)
Example
(125x³ - 8y³) = (5x - 2y) ((5x)² + (5x)(2y) + (2y)²)
= (5x - 2y) (25x² + 10xy + 4y²)
Answer: 1.6
<u>Order the numbers</u>
5,6,6,8,10
<u>Add</u>
5+6+6+8+10=35
<u>Divide</u>
35÷5=7
Mean: 7
Sum divided by the count.
Final Answer: 1.6
Answer:
B) All real values of 'x' where -2 < x< 4
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given function f(x) = (x +2 ) ( x-4)
(x+2)(x-4) =0
⇒ x +2 =0 and x-4=0
⇒ x =-2 and x=4
From graph
Given parabola lies between the x=-2 and x =4
∴ All real values of 'x' lies between x=-2 and x =4
All real values of 'x' lies -2 < x< 4
Answer:
6x^2+10x-6=0
Step-by-step explanation:
First, you need to add all like terms:
6x^2+8x-6=-2x
Now move the -2x to the other side:
6x^2+10x-6=0
Answer: 45% is my guess
Step-by-step explanation: